2018
DOI: 10.1038/s41586-018-0317-6
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of acute myeloid leukaemia risk in healthy individuals

Abstract: The incidence of acute myeloid leukaemia (AML) increases with age and mortality exceeds 90% when diagnosed after age 65. Most cases arise without any detectable early symptoms and patients usually present with the acute complications of bone marrow failure. The onset of such de novo AML cases is typically preceded by the accumulation of somatic mutations in preleukaemic haematopoietic stem and progenitor cells (HSPCs) that undergo clonal expansion. However, recurrent AML mutations also accumulate in HSPCs duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

35
648
4
19

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 678 publications
(706 citation statements)
references
References 47 publications
35
648
4
19
Order By: Relevance
“…Two recent case-control studies showed that preleukemic CH with putative leukemia driver mutations can be found in approximately 70% of blood samples obtained 6 to 9 years before the diagnosis of AML ( Figure 2D). 69,84 Compared to persons with CH who did not develop AML (controls), persons who subsequently progressed to AML (patients) on average had a higher number of CH mutations and, importantly, these variants were present at a higher VAF. While the presence of a single CH-associated mutation in any gene, at a VAF of >1%, was associated with an approximately 5-fold increased risk of AML, co-mutations in two different genes signified a 9-fold risk increase.…”
Section: Ch and Early Detection Of Amlmentioning
confidence: 99%
See 1 more Smart Citation
“…Two recent case-control studies showed that preleukemic CH with putative leukemia driver mutations can be found in approximately 70% of blood samples obtained 6 to 9 years before the diagnosis of AML ( Figure 2D). 69,84 Compared to persons with CH who did not develop AML (controls), persons who subsequently progressed to AML (patients) on average had a higher number of CH mutations and, importantly, these variants were present at a higher VAF. While the presence of a single CH-associated mutation in any gene, at a VAF of >1%, was associated with an approximately 5-fold increased risk of AML, co-mutations in two different genes signified a 9-fold risk increase.…”
Section: Ch and Early Detection Of Amlmentioning
confidence: 99%
“…Interestingly, the authors of one case-control study also found that an increased red blood cell distribution width (a measure of erythrocyte size heterogeneity) distinguished individuals with CH who later developed AML from persons without CH, and, importantly, from those with CH who did not progress. 84 Based on this finding and data routinely available in electronic medical records, the authors used machine learning to develop an AML prediction model that was able to predict AML 6 to 12 months before diagnosis with a sensitivity of around 25% and an overall specificity of >98%. These data indicate that, while there currently is no role for genetic screening for early detection of AML, at least some persons who develop AML have subtle but detectable and quite specific laboratory abnormalities that may allow early detection of the disease before its full-blown clinical manifestation.…”
Section: Ch and Early Detection Of Amlmentioning
confidence: 99%
“…The clonal landscapes of AML bulk populations has been elucidated thanks to the expanding knowledge of driver and passenger mutations (Cancer Genome Atlas Research Network, ; Ho et al , ) including the more recent realisation that such aberrations precede overt disease by years and can be present in normal individuals (Abelson et al , ; Desai et al , ). Thus, during the last 5 years it has become increasingly clear that any attempt to target the AML LSCs has to take into account that: (i) a population of malignant AML cells in a given patient is much more heterogeneous than hitherto believed, and (ii) this heterogeneity is in a flux as the disease progresses and that cytoreduction is going to affect this.…”
Section: Clonal Complexity Of Aml and Its Implications For Lsc Targetingmentioning
confidence: 99%
“…Red blood cell (RBC) distribution width (RDW) describes the size heterogeneity of RBCs and is useful in the differential diagnosis of anaemia. A recent study in healthy individuals reported TP53 and U2AF1 mutations and a high RDW correlated with risk of progression to acute myeloid leukaemia (AML) (Abelson et al , ). Some older persons progress from age‐related clonal haematopoiesis (ARCH) to clonal cytopenia of undetermined significance (CCUS) and on to low‐ and high‐risk MDS before developing AML, and then, we hypothesized that RDW might play a role in MDS.…”
Section: Univariate and Multivariate Analyses In Subjects With Bone Mmentioning
confidence: 99%